Chilling and Heat Stress-Induced Physiological Changes and MicroRNA-Related Mechanism in Sweetpotato (Ipomoea batatas L.) - Yu, Jingjing; Su, Dan; Yang, Dongjing; Dong, Tingting; Tang, Zhonghou; Li, Hongmin; Han, Yonghua; Li, Zongyun; Zhang, Baohong (Frontiers in Plant Science, 2020)
Sweetpotato (Ipomoea batatas (L.) Lam.) is an important industrial and food crop. Both chilling and heat stress inhibits sweetpotato growth and development and then affects yield. However, the physiological and molecular mechanisms of sweetpotato response to chilling and heat stress is unclear. In this study, we investigated the effect of extreme temperature on sweet potato physiological response, with a focus on oxidative stress and the potential microRNA (miRNA)-mediated molecular mechanism. Our results showed that both chilling and heat stress resulted in accumulation of reactive oxygen species, including H2O2 and O2-, and caused oxidative stress in sweetpotato. This further affected the activities of oxidative stress-related enzymes and products, including SOD, POD and MDA. Both chilling and heat stress inhibited POD activities but induced the expression of SOD and MDA, this suggests that sweetpotato cells initiated its own defense mechanism to handle extreme temperature-caused oxidative damage. Oxidative damage and repair are one mechanism that sweetpotato respond to extreme temperatures. Another potential mechanism is miRNA-mediated gene response. Chilling and heat stress induced the aberrant expression of stress-responsive miRNAs. These miRNAs regulate sweetpotato response to extreme stress through targeting individual protein-coding genes.